2017
DOI: 10.1021/acsami.6b14473
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Photothermal Bactericidal Activity of the Reduced Graphene Oxide Modified by Cationic Water-Soluble Conjugated Polymer

Abstract: Surface modification of graphene is extremely important for applications. Here, we report a grafting-through method for grafting water-soluble polythiophenes onto reduced graphene oxide (RGO) sheets. As a result of tailoring of the side chains of the polythiophenes, the modified RGO sheets, that is, RGO-g-P3TOPA and RGO-g-P3TOPS, are positively and negatively charged, respectively. The grafted water-soluble polythiophenes provide the modified RGO sheets with good dispersibility in water and high photothermal c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
63
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(65 citation statements)
references
References 63 publications
2
63
0
Order By: Relevance
“…Xiao and co-workersc ompared the photothermal antibacteriala ctivity of positivelya nd negatively charged rGO composites prepared by covalently graftingp oly[3-(3'-thienyloxy)propyltrimethylammonium bromide] (P3TOPA, ac ationic conjugated polymer) and poly[sodium 3-(3'-thienyloxy)propanesulfonate] (P3TOPS, an anionic conjugatedp olymer). [116] Despite the similar photothermal performance of the as-synthesized RGO-g-P3TOPAa nd RGO-g-P3TOPS, intimatec ontact with bacteria,m ediated by electrostatic attractions, led to a1 6 times highere fficacy of RGO-g-P3TOPA. Moreover,a sd emonstrated in our previous work, nanoparticles with long-alkylchain-linked quaternary ammonium salts have excellent antimicrobial performance with low cytotoxicity towardm ammalian cells.…”
Section: Gm Derivatives and Nanohybrids For Antimicrobial Applicationsmentioning
confidence: 96%
See 1 more Smart Citation
“…Xiao and co-workersc ompared the photothermal antibacteriala ctivity of positivelya nd negatively charged rGO composites prepared by covalently graftingp oly[3-(3'-thienyloxy)propyltrimethylammonium bromide] (P3TOPA, ac ationic conjugated polymer) and poly[sodium 3-(3'-thienyloxy)propanesulfonate] (P3TOPS, an anionic conjugatedp olymer). [116] Despite the similar photothermal performance of the as-synthesized RGO-g-P3TOPAa nd RGO-g-P3TOPS, intimatec ontact with bacteria,m ediated by electrostatic attractions, led to a1 6 times highere fficacy of RGO-g-P3TOPA. Moreover,a sd emonstrated in our previous work, nanoparticles with long-alkylchain-linked quaternary ammonium salts have excellent antimicrobial performance with low cytotoxicity towardm ammalian cells.…”
Section: Gm Derivatives and Nanohybrids For Antimicrobial Applicationsmentioning
confidence: 96%
“…Consequently,G Ms have also been used as nonmetal bactericide carriers to produce GM-metal-free nanohybrids. Antibiotics, [108,109] polymers, [110][111][112][113][114][115][116][117][118] quaternary ammonium/phosphonium salts, [119][120][121] and halogens [122] have been combined with GMs by noncovalent adsorption or chemical conjugation.A bdelhamid et al provedt hat water-soluble antibiotic gramicidin (GD) can be adsorbed by GO through physical interactions and the antibacterial activity of the resultant GOGD is enhanced because of an increased local concentration of GD. [108] Compared with antibiotics, polymers usually cannot efficiently inhibit the growth of microorganisms;h owever,w ith their structure-mediated properties, polymers can enhancet he antimicrobial performance of GMs through different mechanisms.…”
Section: Gm Derivatives and Nanohybrids For Antimicrobial Applicationsmentioning
confidence: 99%
“…In combination of high tumor uptake due to the EPR effect and excellent photothermal conversion capability,N GS-PEG following NIR irradiation could lead to highly effective inhibition of tumor.S ince then, in vitro and in vivo GO-based PTT has been studied in detail by several different groups, in which hydrophilic molecules and functional moieties are covalently or noncovalently functionalized on the surfaceo fG O. [46] The oxidation of graphene causes the damage of p-conjugated structure in the GO, thus, its NIRa bsorption is decreased. The reduction of GO can be used to improvet he PTT efficacy of GO materials.…”
Section: Photothermalt Herapymentioning
confidence: 99%
“…[21][22][23] For instance, graphene (and graphene oxide) has been systematically studied 24 for its antimicrobial activities, [25][26][27][28] along with its underlying molecular mechanisms. [29][30][31][32] It was revealed that graphene and graphene oxide nanosheets can cut into cell membranes, 32 extract large amount of phospholipids, 32 and create holes (pores) on cell membranes, 33 through large scale molecular dynamics simulations.…”
mentioning
confidence: 99%